Testing the validity of the Lorentz factor. (12th July 2018) - Broomfield, H; Hirst, J; Raven, M; Joos, M; Vafeiadis, T; Chung, T K; Harrow, J; Khoo, D; Kwok, T; Li, J; Mandelstam, H; Martin-Halls, J; et al.
Abstract: The CERN Beamline for Schools Competition gives high school students the opportunity to perform an experiment of their design using the T9 facility. Our team, 'Relatively Special', was fortunate enough to be joint winners of this global event and travel to CERN for a unique adventure. This paper gives an account of our story including the application, preparation, experience and the overall effect which it has had on us. We also detail our proposed experiment (Proposal from Relatively Special and Video) which aimed to test the validity of the Lorentz factor with two methods: the time of flight (TOF) of various particles and the decay rate of pions at different momenta. Due to the high sensitivity required for the second method the results were inconclusive, therefore we report only on the results of the first method. We focus on the techniques we used, the setup of detectors, and how they function.